Anti-solvent materials enhanced structural and optical properties on ambiently fabricated perovskite thin films - Nur-E-Alam M.; Islam M.A.; Kar Y.B.; Kiong T.S.; Misran H.; Khandaker M.U.; Fouad Y.; Soudagar M.E.M.; Cuce E. (Nature Research, 2025)
Perovskite solar cells (PSCs) hold potential for low-cost, high-efficiency solar energy, but their sensitivity to moisture limits practical application. Current fabrication requires controlled environments, limiting mass production. Researchers aim to develop stable PSCs with longer lifetimes under ambient conditions. In this research work, we investigated the stability of perovskite films and solar cells fabricated and annealed in natural air using four different anti-solvents: toluene, ethyl acetate, diethyl ether, and chlorobenzene. Films (about 300nm thick) were deposited via single-step spin-coating and subjected to ambient air-atmosphere for up to 30days. We monitored changes in crystallinity, electrical properties, and optics over time. Results showed a gradual degradation in the films? crystallinity, morphology, and electro-optical properties. Notably, films made with ethyl acetate exhibited superior stability compared to other solvents. These findings contribute to advancing stable and high-performance PSCs manufactured under normal ambient conditions. In addition, we also discuss the possible machine learning (ML) approach to our future work direction to optimize the materials structures, and synthesis process parameters for future high-efficient perovskite solar cells fabrication. ? The Author(s) 2024.